We count what we care about: Advancing a framework for valuing investments in active modes. (December 2018) - Piatkowski, Daniel; Marshall, Wesley
Abstract: Transportation investments are traditionally valued through a "mobility-based" transportation planning paradigm focused on user volume. Common metrics include counts, peak hour level of service, peak hour delay, and travel time – and the attention has been almost exclusively on automobile travel. In recent years, more communities are investing in active modes, and with this influx in investments have come pressure to evaluate their impact(s). Bicycle and pedestrian count programs are increasingly called for as they appear to offer a seemingly straightforward metric for valuing investments in active modes. However, this push towards bicycle and pedestrian count programs has come without a theoretical foundation for the role of count data in the planning process. In this paper, we first assess the validity of count data applied to a range of applications in planning for active modes of transportation. We then reflect on the benefits and limitations of count data in the planning process, focusing on the issues related to prioritizing count data as the primary means by which we value investments in active modes. Finally, we propose a new conceptual framework for planning for active modes, making the case for additional metrics that more accurately reflect the myriad benefits of these modes in the planning process.